2018
DOI: 10.1021/acs.macromol.8b01597
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Containing Polymers: Perspectives toward Diverse Applications in Both Adaptive and Biomedical Materials

Abstract: Selenium is a semimetallic element lying in group XVI of the periodic table with its chemical properties resembling sulfur. But owing to its relatively low electronegativity and large atomic radius compared with sulfur, selenium also shows unique properties. This feature endows selenium-containing compounds with high reactivity and sensitivity. Although organic selenium chemistry has been developing very fast, the successful introduction of selenium into polymer science is rather scarce. Fortunately, we have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 109 publications
0
88
0
Order By: Relevance
“…An inorganic selenium‐containing compound selenite (SeO 3 2− ) has been reported to suppress the expression of HLA‐E on cancer cells, thereby rendering them susceptible to NK cells . Since previous studies revealed that the high valence organic selenium‐containing compound seleninic acid exhibited anti‐tumour activity in a similar mechanism to that of selenite, we hypothesize that seleninic acid may also show cancer immunity through NK cell activation. In addition, diselenides have been demonstrated to be sensitive to γ‐radiation .…”
Section: Methodsmentioning
confidence: 93%
“…An inorganic selenium‐containing compound selenite (SeO 3 2− ) has been reported to suppress the expression of HLA‐E on cancer cells, thereby rendering them susceptible to NK cells . Since previous studies revealed that the high valence organic selenium‐containing compound seleninic acid exhibited anti‐tumour activity in a similar mechanism to that of selenite, we hypothesize that seleninic acid may also show cancer immunity through NK cell activation. In addition, diselenides have been demonstrated to be sensitive to γ‐radiation .…”
Section: Methodsmentioning
confidence: 93%
“…Our previous work proved that diselenide bond is a new kind of dynamic covalent bond 57. The low bond energy, which is 172 kJ mol −1 ,58 makes diselenides possible to undergo exchange under the irradiation of visible light without catalyst 59,60. Compared with other DCBs, the diselenide metathesis has a variety of advantages including rapid reaction rate, mild condition, and few by‐products 61.…”
Section: Methodsmentioning
confidence: 99%
“…[13] An inorganic selenium-containing compound selenite (SeO 3 2À ) has been reported to suppress the expression of HLA-E on cancer cells,t hereby rendering them susceptible to NK cells. [14] Since previous studies revealed that the high valence organic selenium-containing compound seleninic acid exhibited anti-tumour activity in as imilar mechanism to that of selenite, [15] we hypothesize that seleninic acid may also show cancer immunity through NK cell activation. In addition, diselenides have been demonstrated to be sensitive to gradiation.…”
mentioning
confidence: 89%